2000
DOI: 10.1080/00219266.2000.9655731
|View full text |Cite
|
Sign up to set email alerts
|

Assessing students' systems reasoning in ecology

Abstract: In this study, several assessment rubrics were used to analyse students' systems reasoning about food web perturbations and pollutant effects within ecosystems. An analytic paper/pencil task and a constructive interview task prompted the reasoning of two classes of 11 year old students (n = 52), before and after they participated in a month-long, hands-on unit in which they constructed, observed, and manipulated mini-ecosystems. When analysing population dynamics in response to perturbations within a food web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 12 publications
4
80
0
15
Order By: Relevance
“…Similar approaches of content analysing, coding and classifying responses to tasks within an environmental context, are considered common in ecological education literature (Grotzer & Bell Basca, 2003;Hogan, 2000;Korfiatis et al, 2004) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar approaches of content analysing, coding and classifying responses to tasks within an environmental context, are considered common in ecological education literature (Grotzer & Bell Basca, 2003;Hogan, 2000;Korfiatis et al, 2004) …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the idea that one change can produce a short term effect which can equilibrate over time or which can then feedback to influence the change that produced it involved reasoning skills that seemed to complex for the children. The repeatedly reported failures to improve this type of skill with children of this age (Grotzer & Bell Basca, 2003;Hogan, 2000;Sheehy et al, 2000), should make us consider the possibility of cognitive development barriers that have to be researched more thoroughly in establishing the objectives of future learning strategies. In educational design studies, the identification of difficulties encountered by students during the process of learning is an important finding since it provides useful input to curriculum developers and also indicates the need to search for underlying causes.…”
Section: Ii) Accessing Systemic Thinkingmentioning
confidence: 99%
“…they believe that living organisms in the ecosystem can affect each other only if they have relation in food chain. Besides, most of high and secondary school students are not aware of the flow of energy among living organisms and they cannot comprehend the proper energy flow in the food chain (Griffiths and Grant, 1985;Hogan, 2000;Özkan et al, 2004;Yörek et al, 2010).…”
Section: Cognitive Structure Research In the Literature About Ecologimentioning
confidence: 99%
“…In this study, when sentences were inspected it was observed that students did not notice food chain is formed by producers, consumers, decomposers and a flow of energy that starts from the sun. Also, Griffiths and Grant (1985), Hogan (2000), Özkan et al (2004) and Yörek et al (2010) determined that students could not comprehend that energy follows in the food chain.…”
Section: Global Warmingmentioning
confidence: 99%
“…Örneğin ekosistemlerin biyotik ve abiyotik öğeleri arasında hiç ilişki olmadığını (Adeneyi, 1985) veya tek yönlü bir ilişki olduğunu (Eilam, 2012;Sander vd., 2006) düşünmektedirler. Hogan (2000)'ın çalışmasında da 11 yaş grubu öğrencilerinin besin ağındaki düzensizliklerle ilgili verdikleri yanıtların, daha karmaşık iki yönlü ve döngüsel ilişkilerden çok, tekyönlü ve doğrusal olduğu saptanmıştır. Bazı çalışmalarda ise öğrencilerin ekosistemde yer alan canlılar arasındaki enerji akışının farkında olmadıkları ve besin zincirindeki doğru enerji akışını kavrayamadıkları (Arkwringht,2014;Griffiths ve Grant, 1985;Hogan, 2000;Özkan vd., 2004;Yörek, vd., 2010) görülmektedir.…”
unclassified